Increasing Critical Thinking through Moral Stories - Malikakhon, Rakhimdjanova (Research Parks Publishers, 2022)
Critical thinking is one of the types of human intellectual activity, which is characterized by a high level of perception, understanding, objectivity of the approach to the information field surrounding it. This term can refer to almost all mental activity. Critical thinking skills-oriented learning involves more than just students actively seeking information to learn, but something more: relating what they have learned to their own experiences, and comparing what they have learned with another research in the field. Students have the right to question the reliability or authority of the information received, check the logic of the evidence, draw conclusions, construct new examples for its application, consider the possibilities of solving the problem, etc. The article describes issues based on increasing critical thinking through moral stories.